Service-based network as a platform: research on a new information communication network architecture - Xiaoyun WANG; Xiaodong DUAN; Tao SUN (Dianxin kexue)
The deployment of 5G enables the network to expand from serving individuals to the industry.The evolution of mobile communication system was analyzed, and a new architecture development direction-service-based network as a platform was proposed.Facing the fundamental challenge of diversified requirements of industrial scenarios, the new architecture employed “platform” to address the generalization and scalability obstacles, and employed “service” to address heterogeneous characteristics of the network.The network service level assurance could also be guaranteed.The definition, overall architecture and mathematical model of “service-based network as a platform” were given.Based on the innovative practice of 5G service-based architecture (SBA) design, the principles of service design were proposed, and then the hierarchical design ideas were given.